Strategi Manajemen Sumber Daya Manusia Dalam Peningkatan Mutu Pendidikan Di SMA Negeri 1 Gamping (Edugama: Jurnal Kependidikan dan Sosial Keagamaan, 2022)
AbstractWith  existence  management  source  power  man  Becomes very important and main  because  success  in  education  based on on usage  source  power  man  that is  head  school and teacher, so that  quality which generated  have  standard  education  quality and quality .  At SMA Negeri 1 Gamping  existence teacher still  not yet  maximum and effective  in  enhancement  quality  education , because  existence  imbalance  leveled  education on Thing  this  that is  placement  educator and power  education which not enough  in accordance  with  his profession . It  cause  lack of  source  power  man  that is teacher. Though  there is  factors  blocker  planning source  power  man at SMA Negeri 1 Gamping   like  lack of  Source  power  man , facility  not enough  adequate , discipline  as well as  work  same  in  doing program and activity which has  made . however  because  existence  commitment which strong  from  head  school  for  doing  planning HR, as well as  existence  spirit which tall  from  tall  from  Head  School , student , and guardian marid so that  until  moment  this  planning source  power  man for  increase  quality  education at SMA Negeri 1 Gamping  still  could  done  with  good , although  still  need  upgraded . In the  study  this   goal  for  study and find  planning source  power  man   in  enhancement  quality at SMA Negeri 1 Gamping , and factor which influence  planning source  power  man   at SMA Negeri 1 Gamping   as well as  study and find  problem and obstacle  in  planning source  power  man   at SMA Negeri 1 Gamping  as well as  find  solution  from  problem and obstacle  the  knowing  is  source  power  man  who there is  at school  already  maximum and effective  for  increase  quality  education .  Keywords: human resources, principals, quality of education, graduate quality dan planning.